1990
DOI: 10.1073/pnas.87.17.6791
|View full text |Cite
|
Sign up to set email alerts
|

Allele loss on chromosome 16 associated with progression of human hepatocellular carcinoma.

Abstract: Loss of heterozygosity on chromosome 16 is a common genetic alteration in human hepatocellular carcinoma (HCC). To clarify the pathogenetic significance of allele loss on chromosome 16, we performed restriction fragment length polymorphism analysis of 70 surgically resected tumors by using 15 polymorphic DNA markers for chromosome 16. Loss of heterozygosity on chromosome 16 was detected in 36 (52%) of 69 informative cases, and the common region of allele loss in these 36 tumors was located between the HP locus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
145
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(155 citation statements)
references
References 53 publications
9
145
0
1
Order By: Relevance
“…Loss of heterozygosity at 1p appears to occur at an early stage of carcinogenesis, and loss of heterozygosity at 16q is associated with progression of HCC. 22,23 Our present results together with those of other studies suggest that FGR/SRC2 and CYLD are associated with hepatocarcinogenesis.…”
Section: Discussionsupporting
confidence: 86%
“…Loss of heterozygosity at 1p appears to occur at an early stage of carcinogenesis, and loss of heterozygosity at 16q is associated with progression of HCC. 22,23 Our present results together with those of other studies suggest that FGR/SRC2 and CYLD are associated with hepatocarcinogenesis.…”
Section: Discussionsupporting
confidence: 86%
“…Chromosome 16q demonstrated LOH in 54% of the tested ERMS between the markers D16S752 and D16S539 on chromosome band 16q23-16qter. Chromosome 16q is also frequently a ected in Wilms' tumors, 20% (Maw et al, 1992), hepatocellular carcinoma, 30% (Tsuda et al, 1990), prostate, 30% (Carter et al, 1990) and breast cancers, 52% (Tsuda et al, 1994). Recently, Weber-Hall et al (1996) demonstrated 16q LOH in 40% of the tested ERMS by comparative genomic hybridization which con®rms our allelotype data.…”
Section: Discussionsupporting
confidence: 85%
“…LOH of chromosome 16q was observed in a variety of human cancers and reported to be associated with the progression of HCC, suggesting the loss of some genes in this region may be involved in the enhancement of tumor aggressiveness [29]. The common deletion region on 16q could be defined to 16q21-q23 (between D16S503 and D16S3091), as shown in this study.…”
Section: Discussionsupporting
confidence: 67%